Balustrade around inner dome - Ghosh, Ayan (Jio Institute, 2023)
Though artificially illuminated now, the inner dome was originally ventilated with natural light entering through large portholes. The dome has a balustrade running around its perimeter from where visitors can look down to the entrance gallery and grand staircase below. A running band of floral motifs carved in stucco adorn the base of the perimeter.